Comparative analysis of thoracic and abdominal aortic aneurysms across the segment and species at the single-cell level - Wu, Hong; Xie, Cheng; Wang, Ruilin; Cheng, Jun; Xu, Qingbo; Zhao, Haige (Frontiers in Pharmacology, 2023)
Aortic aneurysm is a life-threatening condition resulted from progressive dilatation of the aorta, which can be subdivided into thoracic and abdominal aortic aneurysms. Aortic aneurysms in mice can be induced by angiotensin Ⅱ infusion. However, the relevance of using angiotensin Ⅱ induction model to study aneurysm disease and the degree of commonality between species remain elusive. Here, we compared aneurysmal aortic cell populations between mice and humans by single cell RNA sequencing analysis. We revealed similarities and differences of changes in the components of human and murine cell types, and our unbiased comparison between mouse and human identified well conserved subpopulations of SMCs and macrophages. Furthermore, the results of our comparative analyses suggested different biological functions and distinct potential pathogenic genes for thoracic and abdominal aortic aneurysms. MIF and SPP1 signaling networks participated in aortic aneurysm in both organisms. This study determines the aortic aneurysm landscape and sets the stage for future investigations into the potential of subpopulations or marker genes as therapy targets.